2003
DOI: 10.1007/s00228-003-0696-x
|View full text |Cite
|
Sign up to set email alerts
|

Validity of performance indicators for assessing prescribing quality: the case of asthma

Abstract: Validity of performance indicators for assessing prescribing quality Pont, LG; Denig, P; van der Molen, T; van der Veen, WJ; Haaijer-Ruskamp, FM Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim. Abstract Objectives: The aim of this study was to assess the concurrent validity between the identification of suboptimal treatment based on clinical information and computer generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…This study shows their perceived value and feasibility may vary by prescribing topic,34 42 and any research or NHS use of prescribing indicators for improvement would therefore benefit from piloting and evaluation. Some prescribing topics, such as NSAIDs, may be suitable for low-intensity interventions based on repeated feedback using existing electronic data, simple education and possibly small financial incentives but other prescribing topics, such as ‘asthma control’ and ‘antithrombotics in AF’ may require prior work to clean electronic data and refine measures, or more intensive educational work to persuade practices what is being measured is important, or more intensive facilitation of change.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This study shows their perceived value and feasibility may vary by prescribing topic,34 42 and any research or NHS use of prescribing indicators for improvement would therefore benefit from piloting and evaluation. Some prescribing topics, such as NSAIDs, may be suitable for low-intensity interventions based on repeated feedback using existing electronic data, simple education and possibly small financial incentives but other prescribing topics, such as ‘asthma control’ and ‘antithrombotics in AF’ may require prior work to clean electronic data and refine measures, or more intensive educational work to persuade practices what is being measured is important, or more intensive facilitation of change.…”
Section: Resultsmentioning
confidence: 96%
“…Although there are many examples of studies developing prescribing measures and establishing their face and content validity,5 30–33 few have reported the extent to which such measures can identify actual opportunities for improvement 34 35. A Dutch study found that patients identified by a measure-targeting underuse of inhaled corticosteroids in asthma (using prescriptions of short-acting β agonists as a proxy for uncontrolled asthma), 46% were candidates for inhaled steroids after a face-to-face review by a clinician, compared with 25% at best (assuming all ‘further investigations’ would confirm the need for inhaled steroids).…”
Section: Discussionmentioning
confidence: 99%
“…Prescribing medications is one of the most important therapeutic activities of a general practitioner (GP) and the quality of such practices is a relevant issue [1]. There are many determinants that can affect attitudes towards prescribing drugs, such as patients' socio-demographic variables, and the GPs' characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The information on quality of health care is being demanded by policy makers, healthcare professionals and the general public 3 . Standards setting and assessment of the quality care through performance review should be part of everyday practice 4 .…”
Section: Introductionmentioning
confidence: 99%